A relationship between temperature and aggression in NFL football penalties - Curtis Craig; Randy W. Overbeek; Miles V. Condon; Shannon B. Rinaldo (Elsevier, 2016)
Background: Increased ambient temperature has been implicated in increased physical aggression, which has important practical consequences. The present study investigates this established relationship between aggressive behavior and ambient temperature in the highly aggressive context of professional football in the National Football League (NFL). Methods: Using a publicly available dataset, authors conducted multiple hierarchical regression analyses on game-level data (2326 games). Results: The analysis revealed that temperature positively predicted aggressive penalties in football, and that this relationship was significant for teams playing at home but not for visiting teams. Conclusion: These results indicate that even in the aggressive context of football, warmer weather contributes to increased violence. Further, the presence of the heat-aggression relationship for the home team suggests that the characteristics of interacting groups may influence whether heat would have an adverse effect on the outcome of those interactions.